Lateral/basolateral amygdala serotonin type-2 receptors modulate operant self-administration of a sweetened ethanol solution via inhibition of principal neuron activity - Mccool, Brian; Christian, Daniel; Fetzer, Jonathan; Chappell, Ann (Frontiers in Integrative Neuroscience, 2014)
The lateral/basolateral amygdala (BLA) forms an integral part of the neural circuitry controlling innate anxiety and learned fear. More recently, BLA dependent modulation of self-administration behaviors suggests a much broader role in the regulation of reward evaluation. To test this, we employed a self-administration paradigm that procedurally segregates ‘seeking’ (exemplified as lever-press behaviors) from consumption (drinking) directed at a sweetened ethanol solution. Microinjection of the nonselective serotonin type-2 receptor agonist, alpha-methyl-5-hydroxytryptamine (-m5HT) into the BLA reduced lever pressing behaviors in a dose-dependent fashion. This was associated with a significant reduction in the number of response-bouts expressed during non-reinforced sessions without altering the size of a bout or the rate of responding. Conversely, intra-BLA -m5HT only modestly effected consumption-related behaviors; the highest dose reduced the total time spent consuming a sweetened ethanol solution but did not inhibit the total number of licks, number of lick bouts, or amount of solution consumed during a session. In vitro neurophysiological characterization of BLA synaptic responses showed that -m5HT significantly reduced extracellular field potentials. This was blocked by the 5-HT2A/C antagonist ketanserin suggesting that 5-HT2-like receptors mediate the behavioral effect of -m5HT. During whole-cell patch current-clamp recordings, we subsequently found that -m5HT increased action potential threshold and hyperpolarized the resting membrane potential of BLA pyramidal neurons. Together, our findings show that the activation of BLA 5-HT2A/C receptors inhibits behaviors related to reward-seeking by suppressing BLA principal neuron activity. These data are consistent with the hypothesis that the BLA modulates reward-related behaviors and provides specific insight into BLA contributions during operant self-administration of a sweetened ethanol solution.